Peran Badan Pemeriksa Keuangan dalam Penguatan Akuntabilitas Keuangan Daerah: Analisis Efektivitas Audit dan Tindak Lanjut Rekomendasi di Provinsi Jawa Tengah - Dinda Azzahra Putri; Mulyati Rahmah; Putri Aulia Khairani; Revi Haryanti; Sri Permata Putri; Jumiati; Boni Saputra (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This study investigates the role of the Audit Board of Indonesia (BPK), particularly its Representative Office in Central Java Province, in enhancing accountability in regional financial management through a literature review approach. Regional financial accountability serves as a crucial indicator for achieving good governance. The analysis explores relevant literature concerning BPK’s functions in auditing processes, issuance of audit opinions, and follow-up actions. The review finds that BPK plays a strategic role in fostering transparency and accountability through its independent and objective audit mechanisms. BPK’s audit findings contribute to improving the quality of regional financial reporting and strengthening internal control systems. The study recommends enhancing institutional capacity and promoting stronger synergy between BPK and local governments to achieve more accountable financial governance.